2018
DOI: 10.1051/shsconf/20184801026
|View full text |Cite
|
Sign up to set email alerts
|

Determining the learning preferences of the students of the faculty of health sciences in Cyprus International University

Abstract: Abstract. The purpose of the study is to examine the learning preferences of students at the Cyprus International University of Health Sciences and determine whether these preferences have changed according to department and sex. A total of 150 students participated in the study. While 61 of the students were female and 89 were male, the mean age was 22.06 ± 1.23 years. VARK [Visual, Aural, Read-write, Kinesthetic] Learning Preferences Inventory was used to determine students' learning preferences. As a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…Similarly, kinaesthetic mode of learning is highly preferred by Gen Z undergraduates in most of the programmes of study except BHMS and B. Pharm undergraduates. In conjunction with this study, a previous study among Physical Therapy and Rehabilitation and Nursing students also found a preference for kinaesthetic learning, however, in the same research, the researchers found that the Nutrition and Dietetic students preferred the auditory style (Cetin & Erel, 2018).…”
Section: Influence Of Programme In Learning Preferencessupporting
confidence: 73%
“…Similarly, kinaesthetic mode of learning is highly preferred by Gen Z undergraduates in most of the programmes of study except BHMS and B. Pharm undergraduates. In conjunction with this study, a previous study among Physical Therapy and Rehabilitation and Nursing students also found a preference for kinaesthetic learning, however, in the same research, the researchers found that the Nutrition and Dietetic students preferred the auditory style (Cetin & Erel, 2018).…”
Section: Influence Of Programme In Learning Preferencessupporting
confidence: 73%
“…Similar results were found in some of the previously conducted studies (AlKhasawneh, 2013;Braakhuis et al, 2015;Türker, 2017). Although learning styles differed in terms of the faculties the students were studying in, their dominant learning styles were found to be aural and kinesthetic learning styles in general (Cetin & Erel, 2018;Powers, 2016;Wong, Siow, Kumarasamy, & Suhaimi, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…McGraw-Hill Education [53]; Rogowski et al [54]; Vagg et al [55]; Severiens and Ten Dam [56]; Keri [57]; Francis [58]; Alkhasawneh et al [59]; Demirbas and Demirkan [60]; Sarabi-Asiabar et al [61]; Al-Saud [62]; Cetin and Erel [63]; Dalmolin et al [64]; Othman et al [65]; Demirkan [66]; Matthews [67]; Garber [68]; Yousef [69]; Gappi [70]; Kolb [71]; Felder and Soloman [72].…”
Section: Studies On Online Learning and Knowledge-based Educational Environmentmentioning
confidence: 99%
“…There is very little information on the learning preferences of students related to gender and education level that could be extrapolated into generic managerial strategies through the lenses of knowledge management. Previous studies on students learning preferences are older [56][57][58][59][60], do not cover current digital preferences or are individualized to specific fields of activity, such as medicine and health [61][62][63][64], mathematics [65], interior architecture [66], etc. Matthews revealed a significant difference among learning styles according to the discipline of study [67], while Severiens and Dam [56] emphasized the context's role in influencing the learning preferences of female and male students.…”
Section: Studies On Digitally Driven Student Transformationmentioning
confidence: 99%